2022
DOI: 10.25157/j-kip.v3i2.6302
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Campuran Ekstrak Daun Kenikir Dan Daun Sirih Terhadap Penyembuhan Luka Sayat Pada Mencit

Abstract: Penggunaan bahan kimia pada proses penyembuhan luka dapat menimbulkan efek samping sehingga perlu adanyaalternative yang lebih aman. Salah satunya yaitu daun kenikir (Cosmos caudatus) yangmengandung senyawa aktif yaituflavonoid, tanin, saponin dan daun sirih hijau (Piper betle.)yang mengandung senyawa aktif yaitu flavonoid, saponin,tanin, dan minyak atsiri. Senyawa tersebut berperan aktif dalam penyembuhan luka sayat. Tujuan penelitian ini adalahuntuk mengetahui pengaruh campuran ekstrak daun kenikir dan daun … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In the initial phenomenon, it has been explained that normally, the wound undergoes a healing process and is a response of connective tissue that occurs in three phases that can overlap, namely the process of inflammation (inflammatory phase), the process of building new tissue (proliferative phase), and the process of strengthening the tissue (maturation or remodeling phase). 5 Open wounds such as cuts are very susceptible to infection, especially by bacteria, and can be an entry point for systemic infections, therefore requiring wound care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the initial phenomenon, it has been explained that normally, the wound undergoes a healing process and is a response of connective tissue that occurs in three phases that can overlap, namely the process of inflammation (inflammatory phase), the process of building new tissue (proliferative phase), and the process of strengthening the tissue (maturation or remodeling phase). 5 Open wounds such as cuts are very susceptible to infection, especially by bacteria, and can be an entry point for systemic infections, therefore requiring wound care.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the wound healing process is divided into three overlapping phases: the inflammation phase, new tissue formation phase (proliferative phase), and tissue strengthening phase (maturation or remodeling phase). 3,5,6 Wound healing is important because the skin has specific functions in the body, including protective, sensory, thermoregulatory, metabolic, and sexual signaling. These functions cannot operate as they should when a wound occurs.…”
Section: Introductionmentioning
confidence: 99%
“…The 30% concentration was more influential on its use as a wound medicine than the other concentrations (20%, 40%, and distilled water extracts). Research by Afrylyani et al 25 showed that a mixture of kenikir and green betel leaf extracts had an effect on wound healing in mice with the most effective concentration being the concentration of 7.5% kenikir leaf extract + 7.5% green betel. Gantriani et al 26 showed that an ethanol extract of green betel leaves at a concentration of 10% was effective in accelerating the healing time of incision wounds in male white Wistar rats compared to other therapy groups (concentrations of 20%, 40%, and povidone iodine).…”
Section: Introductionmentioning
confidence: 99%